Contemporary linguistics: integrating languages, communities, and technologies - Bradley, David; Dziubalska-Kołaczyk, Katarzyna; Hamans, Camiel; Yi, Ik-hwan; Steurs, Frieda; Hu, Linda; Warren, Noah (BRILL, 2025)
"The International Congress of Linguists, ICL, takes place every five years. It is the meeting where the world's leading linguists present their research and discuss the progress of their work and the state of their profession. 21st ICL Poznań 2024 is a highlight in this series. In twelve plenary lectures, eighteen extensive sections and twelve focus streams, two special panels and numerous workshops, all theories and schools, new developments and emerging sub-disciplines of linguistics are discussed. This book contains the plenary lectures and all introductions to the sections and focus streams that cover special areas of interest and thus offers the State of the Art of linguistics in 2024"-- Provided by publisher